Near UV-light excitable SrAl2O4:Eu3þ nanophosphors for display device applications - Ashwini, K.R. (H. : ĐHQGHN, 2020)
Near UV-light excitable inorganic phosphors are widely recommended for white-light emitting diode (wLED) applications. Here in this paper we prepared Eu3þ doped SrAl2O4 phosphors with various concentrations of Eu3þ (1e5 mol%) by a green combustion technique. The phase structure and purity of all prepared nanopowders (NPs) were studied by X-ray diffraction analysis. The prepared NPs showed a fibre-like morphology which is confirmed by scanning electron microscopy results. The particle size as obtained by the transmission electron microscopy results is found to be around 40 nm. Further, the elemental composition showed the presence of doped Eu3þ ions into the SrAl2O4 host. The photoluminescence (PL) spectra of Eu3þ ions doped SrAl2O4 compounds are studied in detail. From the PL studies it is observed that the intense peak at 618 nm is due to the 5D0/7F2 transition of Eu3þ ions under 393 nm (near UV-light) excitation wavelength. The emission color and the chromaticity values of the NPs are studied, which suggest a strong red emission. The average estimated co-related temperature value is observed to be ~2688 K. This temperature value indicates that these phosphor powders can be used for warm LED applications. The color purity (CP) of the synthesized NPs has been calculated and the value is found to be 88%, which indicates that the prepared phosphor powders are highly useful for the red component in white light emitting diodes under UV light excitation.